TO THE 100th ANNIVERSARY OF VLADIMIR PETROVICH DEMIKHOV. Vladimir Demikhov, a man of an unbending spirit - L. A. Bokerija; S. P. Glyantsev (Вестник трансплантологии и искусственных органов, 2016)
To the 100th anniversary of Vladimir Petrovich Demikhov